The Einstellung effect, mental rigidity and decision-making in startup accelerators (INMR - Innovation & Management Review, 2021)
Purpose – This paper aims to investigate the decision-making on new ventures of eight directors ormanagers of Brazilian accelerators, aiming to understand if the Einstellung effect – mental rigidity – operatesduring the judgment of new ventures to accelerate.Design/methodology/approach – Through a quasi-experiment design, the study was conducted withdirectors or managers of Brazilian accelerators, who were separately interviewed and responded to apsychological test, previously consented, as well as to a simulated decision-making questionnaire.Findings – The selection process, with the criteria for decision-making, functions as a “template” for therecognition of potentially successful companies and is, indeed, subject to various cognitive biases, amongwhich, the Einstellung effect, characteristic of mental rigidity.Research limitations/implications – The main contribution of the present study is to identify thecognitive mechanisms, which can negatively affect the evaluation of innovative projects and propose waysthat can counteract or mitigate them.Originality/value – The psychological approach to decision-making, usually studied in chess gamecontext or problem-solving, was applied to a relatively unexplored field that is startups to accelerate. Itsoriginality remains at the interdisciplinary approach, combining knowledge from psychology, decisionmaking and entrepreneurship